PEMANFAATAN HADĪTH DA’ĪF UNTUK TARGHĪB DAN TARHĪB - Mohammad Subhan Zamzami (LP2M IAI Miftahul Ulum Pamekasan, 2015)
This article attempts to study some opinions of Muslim scholars and their arguments about applying of weak hadīths (hadīth da’īf) for stimulus to do any virtues (targhīb) and for prevention to do any evils (tarhīb). It also gives examples of weak hadīths applied for both cases and explains their weakness according to Muslim scholars’ judgments. Based on their opinions and judgments, it encourages Muslim activists to beware in using any kinds of hadīths for their religious preaching ",